Hybrid Precoding Design for Two Carriers Aggregated in 5g Massive Mimo System - Soto-Gomez, J; Adasme-Soto, P (Institute of Electrical and Electronics Engineers Inc., 2020)
Hybrid digital and analog beamforming are today widely research topics in massive MIMO systems due to low cost and low power consumption as compared to conventional fully digital beamforming method. The beamforming matrix consists of analog radio frequency (RF) precoder and it is implemented by using phase shifters and baseband digital precoder. Carrier aggregation (CA) is a technology that allows bandwidth expansion to improve data capacity by combining two or more carriers in the same or different frequency bands. The digital baseband precoder is the main challenge and can be adapted to the channel of each carrier in the frequency domain while the same analog RF precoder must be applied to all carriers simultaneously in the time domain. The main goal of our research is to combine CA technology with hybrid digital and analog beamforming architecture to provide an improved system performance with less penalty. This paper proposes a hybrid precoding algorithm to support two carriers aggregated that are based on this scenario. We present numerical results that prove theoretical expressions and give practical explanation of the proposed method demonstrating its superiority when compared to the traditional hybrid beamforming design. © 2020 IEEE.